2009
DOI: 10.1097/yic.0b013e328329b199
|View full text |Cite
|
Sign up to set email alerts
|

Adverse event load in bipolar participants receiving either carbamazepine immediate-release or extended-release capsules: a blinded, randomized study

Abstract: In epilepsy, slow-release formulations of carbamazepine (CBZ) have fewer adverse events (AEs) compared with immediate-release (IR) formulations. As CBZ is used for mania, it is important to determine whether a similar pattern exists for bipolar patients. This was a 3-month, blinded, random-assignment study to an IR formulation or extended-release carbamazepine capsules (ERCC, Equetro) in type I or type II bipolar patients already on CBZ or clinically determined to benefit from it. Dosages were titrated to pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A small RCT in 44 patients with manic, mixed, or depressive episodes found that among patients who were on, or thought to benefit from, carbamazepine, there were no differences in mood ratings or in the total level of adverse events with immediate-release versus ER carbamazepine (63,64). However, there were significantly fewer autonomic and gastrointestinal adverse events with carbamazepine ER (64).…”
Section: Pharmacological Treatment Of Manic Episodesmentioning
confidence: 99%
See 2 more Smart Citations
“…A small RCT in 44 patients with manic, mixed, or depressive episodes found that among patients who were on, or thought to benefit from, carbamazepine, there were no differences in mood ratings or in the total level of adverse events with immediate-release versus ER carbamazepine (63,64). However, there were significantly fewer autonomic and gastrointestinal adverse events with carbamazepine ER (64).…”
Section: Pharmacological Treatment Of Manic Episodesmentioning
confidence: 99%
“…There is additional evidence to support the use of carbamazepine (level 2), as a small RCT in a mixed population of 44 patients with BD found that ER carbamazepine was as effective as the immediate-release form, with fewer autonomic and gastrointestinal adverse events (63,64).…”
Section: Quetiapine + Lamotriginementioning
confidence: 99%
See 1 more Smart Citation
“…Serum carbamazepine levels fluctuate considerably, even with multiple daily doses (30,31) and can be associated with transient adverse effects at peak concentrations (31–33). Tolerability and even seizure control have been reported to improve with extended‐release carbamazepine, typically given twice daily (34–36), and some of these findings have been confirmed in blinded randomized trials (37,38). The value of extended‐release carbamazepine is further suggested by the results of two recent double‐blind studies that compared lamotrigine with carbamazepine among elderly patients with new‐onset epilepsy (39,40).…”
Section: Extended‐release Formulations Of Different Aeds: Are They Eqmentioning
confidence: 99%